Effective food and nutrition policy responses to HIV/AIDS: what we know and what we need to know - Haddad, Lawrence J.; Gillespie, Stuart (Wiley, 2001)
This paper addresses the broad question: ‘How should government policies in the area of food security, nutrition, agriculture and the environment be altered to better meet the needs of the poor within the context of the HIV/AIDS pandemic?’ We review the literature on the impact of HIV/AIDS on livelihoods, with special reference to agriculture, food security and nutrition. We highlight public policy options for effective HIV/AIDS mitigation in the areas of agriculture and nutrition and discuss the role of research in stimulating effective action for AIDS mitigation and ultimately for HIV prevention. The review concludes with a consideration of research priorities. Copyright © 2001 John Wiley & Sons, Ltd.